Mozambique Agricultural Sector Risk Assessment : Risk Prioritization - Suit, Kilara C. (World Bank, Washington, DC, 2015)
Agricultural risk management is a central issue that Mozambique faces in development, and multiple stakeholders have analyzed this challenge, sometimes with different terminology and focusing on varying aspects. The government of Mozambique has adopted the strategic plan for agricultural development (PEDSA 2010-19) that focuses on: (i) increasing the availability of food in order to reduce hunger through growth in small producer productivity and emergency response capacity; (ii) enlarging the land area under sustainable management and the number of reliable water management systems; (iii) increasing access to the market through improved infrastructures and interventions in marketing; and (iv) improving research and extension for increased adoption of appropriate technologies by producers and agro-processors. The World Bank’s agriculture sector risk assessment takes a holistic approach and relies on long time-series historical data to arrive at an empirical and objective assessment of agricultural risks and their impacts on Mozambique. This assessment will form the basis of the second step, solution assessment, whose final findings will inform National Investment Plan for the Agrarian Sector in Mozambique (PNISA). This document considers the many aspects of assessing risk in the Mozambican agriculture sector. Chapter one gives introduction and context. Chapter two introduces the major characteristics of the agricultural system leading into chapter three, which presents a comprehensive picture of the risks that exist in the sector. Chapter four, in quantifying the risks that have been observed, comments on the losses that have been incurred by the sector because of production risks, whereas chapter five provides a qualitative discussion of how risk has an effect on the different stakeholders present in the sector. Chapter six delves into the risk prioritization carried out by the team and then comments on various management measures. The report concludes with chapter six, in which recommendations are provided for improving risk management in Mozambique.